2015
DOI: 10.1111/jam.12967
|View full text |Cite
|
Sign up to set email alerts
|

A systematic comparison of antimicrobial wound dressings using a planktonic cell and an immobilized cell model

Abstract: Aim: The aim of the study was to evaluate the ability of in-vitro planktonic and immobilised cell models for determining the antimicrobial efficacy of common antimicrobial wound dressings.Methods and Results: Five strains of A.baumannii, P.aeruginosa and S. aureus (MRSA) were tested against four antimicrobial wound dressings containing silver, honey or PHMB, Significance and Impact of study: The introduction of planktonic and immobilised cell models as part of testing regimens for wound dressings will provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Our data indicate that PHMB did not significantly reduce bacterial counts, in contrast to previous studies using planktonic culture, single and mixed biofilms treated statically, which showed significant reduction in bioburden (Lipp et al, 2010; Rembe et al, 2016). Models in which bacteria are immobilized in a collagen matrix that better represents the biofilm environment suggest that the efficacy of PHMB has been overestimated with smaller reductions in bacterial bioburden in agreement with our results (Shoukat et al, 2015). Crystal or gentian violet (CV/GV) was re‐evaluated in 1992 as a dermatological antiseptic and approved by FDA in 2013 for the treatment of diabetic foot ulcers and pressure ulcers, both of which are classed as chronic wounds (Edwards, 2016; Maley & Arbiser, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Our data indicate that PHMB did not significantly reduce bacterial counts, in contrast to previous studies using planktonic culture, single and mixed biofilms treated statically, which showed significant reduction in bioburden (Lipp et al, 2010; Rembe et al, 2016). Models in which bacteria are immobilized in a collagen matrix that better represents the biofilm environment suggest that the efficacy of PHMB has been overestimated with smaller reductions in bacterial bioburden in agreement with our results (Shoukat et al, 2015). Crystal or gentian violet (CV/GV) was re‐evaluated in 1992 as a dermatological antiseptic and approved by FDA in 2013 for the treatment of diabetic foot ulcers and pressure ulcers, both of which are classed as chronic wounds (Edwards, 2016; Maley & Arbiser, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Within the same study, the lowest values consistently corresponded to the Gram-negative bacteria Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli), and the highest to the Gram-positive bacteria Pseudomonas aeruginosa (P. aeruginosa). MIC and MBC values may be higher when bacteria form biofilms, as suggested by the results of a study that show that the antimicrobial activity of a commercial PRWD was higher in a planktonic cell model than in an immobilized cell model used to mimic biofilms [49]. PHMB is well tolerated when administered topically to wounds, showing low cytotoxicity and poor skin penetration [28,44,50], and also promotes wound healing, by favoring tissue granulation on the wound surface [5].…”
Section: The Antiseptic Polyhexanide (Phmb)mentioning
confidence: 99%
“…Almost all of the reported in vitro antibacterial activity assays with PRMs employed single bacterial cultures in planktonic form or as colonies on agar (Table 8). As in chronic wounds, bacteria are present as mixed-species biofilms [189] and as PHMB is less effective when bacteria are present in biofilm form [49], these are not the most relevant types of bacterial cultures to model bacteria in chronic wounds. Additionally, the effect of exudate has to be considered, since commercial AMDs, including PRWDs, have shown reduced antimicrobial activity when evaluated in vitro in the presence of human wound exudate [87].…”
Section: Prm23amentioning
confidence: 99%
“…Within a same study, the lowest values consistently corresponded to the Gram-negative bacteria Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli), and the highest to the Gram-positive bacteria Pseudomonas aeruginosa (P. aeruginosa). MIC and MBC values may be higher when bacteria form biofilms, as suggested by the results of a study showing that the antimicrobial activity of a commercial PRWD was higher in a planktonic cell model than in an immobilized cell model used to mimic biofilms [52]. PHMB is well tolerated when administered topically to wounds, showing low cytotoxicity and poor skin penetration [28,44,53], and also promotes wound healing, by favoring tissue granulation on the wound surface [5].…”
Section: The Antiseptic Polyhexanide (Phmb)mentioning
confidence: 99%
“…Almost all reported in vitro antibacterial activity assays with the novel PRMs employed single bacterial cultures in planktonic form or as colonies on agar (Table 8). As, in chronic wounds, bacteria are present as mixed-species biofilms [190] and as PHMB is less effective when bacteria are present in biofilm form [52], these are not the most relevant type of bacterial cultures to model bacteria in chronic wounds. Additionally, the effect of exudate has to be considered, since commercial AMDs, including PRWDs, have shown reduced antimicrobial activity when evaluated in vitro in the presence of human wound exudate [71].…”
Section: Prm23amentioning
confidence: 99%